2015
DOI: 10.1016/j.bbamcr.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2 promotes the migration and invasion of esophageal squamous cell carcinoma cells through a novel positive feedback loop

Abstract: Lipocalin 2 (LCN2) is a poor prognostic factor in esophageal squamous cell carcinoma (ESCC), however its functional roles and molecular mechanisms of action remain to be clarified. Here, we described the functions and signaling pathways for LCN2 in ESCC. Overexpression of LCN2 in ESCC cells accelerated cell migration and invasion in vitro, and promoted lung metastasis in vivo. Blocking LCN2 expression inhibited its pro-oncogenic effect. Either overexpression of LCN2 or treatment with recombinant human LCN2 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…Elevated expression of NGAL can increase the invasiveness of certain cancer cells, while inhibition of NGAL expression decreases their invasiveness and metastasis [81,91,96,97]. New approaches to target MMP-9/NGAL are needed as MMP-9 inhibitors have not performed well in clinical cancer trials [98].…”
Section: Effects Of Ngal On Cancer Progressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated expression of NGAL can increase the invasiveness of certain cancer cells, while inhibition of NGAL expression decreases their invasiveness and metastasis [81,91,96,97]. New approaches to target MMP-9/NGAL are needed as MMP-9 inhibitors have not performed well in clinical cancer trials [98].…”
Section: Effects Of Ngal On Cancer Progressionmentioning
confidence: 99%
“…Many transcription factors, including the estrogen and androgen receptors, regulate NGAL expression by both positive and negative mechanisms [67][68][69][70][71][72][73][74][75][76][77]. 11 NGAL is an important molecule in many different types of cancer including: breast [9,10,77], colorectal (CRC) [78,79], endometrial [80], esophageal [7,81], gastric cancer [6], liver [82][83][84], lung [85][86][87] ovarian [88], pancreatic [89,90], prostate [76,91], renal [8,92] and thyroid cancer [68]. In general, elevated NGAL expression has been associated with advanced cancer and poor prognosis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous experiments carried out in cellular and murine cancer models have also demonstrated a role of NGAL in cell migration and invasion (30)(31)(32).…”
Section: Chemotactic Role Of Ngalmentioning
confidence: 99%
“…Cytokine array analysis between parent KYSE150 cells and LuM cells demonstrated that several cytokines were up-regulated in the supernatant of LuM cells compared with that of parent KYSE150 cells (Figure 3C, Table 1). Among these up-regulated proteins, we focused on LCN2, since it was previously shown to promote the migration and invasion of ESCC cells [12]. The expression level of LCN2 protein was higher in both the cell lysate and the supernatant of LuM cells than in those of parent KYSE150 cells (Figure 3D and 3E).…”
Section: Resultsmentioning
confidence: 98%